Semantic Fields: Formal Modelling and Interlanguage Comparison. Issue 1 (2nd January 2017) - Dullieva, Karina
Abstract: The research deals with a semantic field constructing method and comparative analysis of two semantic fields. Semantic features of lexemes are on the basis of creating an abstract model of concept that semantically unites all the units of compared semantic fields. The method of contrasting semantic fields is on the basis of "abstractness-concreteness", which can give quantitative estimate of differences between semantic fields. Cooking verbs semantic fields are taken into consideration. It is shown that the semantic field of cooking verbs in English is more specific compared with that in Russian.